TEOLOGI PASTORAL SEBAGAI REFLEKSI PELAYANAN PASTORAL MENURUT 1 PETRUS 5:1-4 - Marojahan Saragi Napitu; Estherina Andhi Juniva; Wikanto; Timotius A. Laana (STT IKSM SANTOSA ASIH, 2025)
Abstract Pastoral theology is a branch of theology that focuses on the perspective of shepherding in all activities and functions of the church and pastors. In this section, the task of shepherding is a task entrusted by God to be carried out according to God's own instructions and provisions. This article aims to provide an understanding of the responsibility of shepherding in the perspective of 1 Peter 5:1-4 and find its implications for shepherding. This writing method uses hermeneutics based on biblical exegesis. The responsibility of the shepherd in 1 Peter 5:1-4 is to serve without being forced, to serve voluntarily, to serve without seeking personal gain, to serve with enthusiasm and to serve by setting an example. Abstrak Teologi pastoral merupakan cabang ilmu teologi berfokus pada perspektif penggembalaan pada semua kegiatan dan fungsi gereja serta pendeta. Dalam bagian ini, tugas penggembalaan adalah tugas yang dipercayakan oleh Allah untuk dilakukan sesuai petunjuk dan ketetapan Allah sendiri. Artikel ini bertujuan untuk memberikan pemahaman tentang tanggungjawab penggembalaan dalam perspektif 1 Petrus 5:1-4 dan menemukan implikasinya bagi penggembalaan. Metode penulisan ini menggunakan hermeneutik berdasarkan eksegesa Alkitab. Adapun tanggung jawab gembala di dalam 1 Petrus 5:1-4 adalah melayani tanpa dengan terpaksa, melayani dengan sukarela, melayani tanpa mencari keuntungan pribadi, melayani dengan semangat dan melayani dengan memberi teladan.